2011
DOI: 10.1155/2011/578163
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Infection and Hodgkin's Lymphoma in South Africa: An Emerging Problem

Abstract: Hodgkin's lymphoma (HL) occurs with increasing frequency in human-immunodeficiency-virus-(HIV-) infected individuals. The natural history and behaviour of HIV-HL is different, being more atypical and aggressive. The association between HIV and HL appears to be primarily EBV driven. HAART use does not significantly impact on the incidence of HL. Indeed, the risk of HL has increased in the post-HAART era. However, the advent of HAART has brought renewed hope, allowing standard therapeutic options to be used more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 39 publications
1
35
0
2
Order By: Relevance
“…It should be emphasized that HIV/AIDS is associated with multiple types of cancer (103), and although the introduction of ART has led to a dramatic improvement in the prognosis of HIV infection, the incidence of cancer in HIVinfected patients has remained high. This is particularly evident in countries with a high incidence of HIV such as South Africa, where HIV and lymphoma comorbidity is a huge societal problem (132,133). Clinical trials of Trx and GSH pathway inhibitors in individuals affected by HIV and lymphoma should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that HIV/AIDS is associated with multiple types of cancer (103), and although the introduction of ART has led to a dramatic improvement in the prognosis of HIV infection, the incidence of cancer in HIVinfected patients has remained high. This is particularly evident in countries with a high incidence of HIV such as South Africa, where HIV and lymphoma comorbidity is a huge societal problem (132,133). Clinical trials of Trx and GSH pathway inhibitors in individuals affected by HIV and lymphoma should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of TB co‐infection has been reported in HIV+ HL locally, but the prevalence of TB in other subtypes and in HIV‐negative patients is unclear. Despite screening many of the lymphoma cases with lymphohistiocytic aggregates and granulomas for AFB, only 1 positive case was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, reports from centers in Kenya, South Africa, and Tanzania all suggest increasing NHL burden since the onset of the HIV epidemic, [9][10][11] with some suggestion that HL is also increasing. 12 Incidence trends for leukemia and multiple myeloma are less clear. However, increasing NHL and HL incidence suggest that GLOBOCAN 2030 projections are significantly underestimated and that lymphoma will increase as a proportional contributor to overall cancer burden in the coming decades.…”
Section: Mutu Umodzi Susenza Denga -"A Single Head Cannot Support a Rmentioning
confidence: 99%
“…Consistent increases in NHL, and to a lesser extent HL, have been noted across the region since the onset of the HIV epidemic, and HIV prevalence among NHL and HL patients in many settings ranges from 30% to 70%. 10,12,[32][33][34] In resource-rich countries, clinical trials and observational cohorts have demonstrated comparable outcomes for HIVassociated NHL and HL to patients without HIV, [35][36][37] whereas others have found HIV to be independently associated with mortality. 38 There are limited data examining the impact of HIV on NHL survival in sub-Saharan Africa, although studies suggest that concurrent ART may render survival similar to patients without HIV.…”
Section: Hivmentioning
confidence: 99%